Effect of High Temperature During First and Second Halves of Incubation on Layer Chicken Embryo Physiology - Nideou , D.; N`nanle, O.; Kouame, Y.A.E.; Chrysostome, C.; Gbeassor, M.; Decuypere, E.; Tona, K. (International Journal of Poultry Science, 2019)
Background and Objective: High incubation temperatures accelerate embryonic growth or increase embryonic mortality depending on incubation stage, duration of exposure. The purpose of this study was to evaluate the influence of high incubation temperature on layer chicken embryo. Materials and Methods: A total of 1200 hatching eggs were studied in two different experiments and divided into two groups, control and high temperature group. Eggs of control group were incubated at standard incubation temperature of 37.6°C. Eggs of high temperature groups were incubated at 38.6°C during the first 10 days for experiment 1 or 18 days for experiment 2. During incubation samples of eggs were used to determine the weights of remaining albumen, embryo and yolk sac. Also, hatching events and hatch were monitored every two hours between 19 and 21 day of incubation. Blood samples were collected at 18 day-old embryo, internal pipping stage and at hatch for tri-iodothyronine, thyroxine and corticosterone level determinations. Results: Results suggested that, the embryos incubated at high temperature during the first 10 days used albumen more rapidly with no effect on hatchability. On contrary, embryos incubated at high temperature during the first 18 days reduced significantly albumen utilization after days 13 of incubation with negative effect on hatchability (p